Isavuconazole Treatment in a Mixed Patient Cohort with Invasive Fungal Infections: Outcome, Tolerability and Clinical Implications of Isavuconazole Plasma Concentrations - Zurl, Christoph (J Fungi (Basel), 2020)
Isavuconazole (ISA) is a triazole antifungal agent recommended for treatment of invasive aspergillosis or mucormycosis. The objective of this study was to evaluate ISA levels in a real world setting in a mixed patient cohort including patients with non-malignant diseases and extracorporeal treatments, and to correlate findings with efficacy and safety outcomes. We investigated 33 ISA treatment courses in 32 adult patients with hematological and other underlying diseases and assessed the clinical response, side effects and ISA trough plasma concentrations. ISA treatment led to complete and partial response in 87% of patients and was well tolerated. The median ISA plasma concentration was 3.05 µg/mL (range 1.38–9.1, IQR 1.93–4.35) in patients without renal replacement therapy (RRT) or extracorporeal membrane oxygenation (ECMO) and significantly lower in patients with RRT including cases with additional ECMO or Cytosorb(®) adsorber therapy (0.88 µg/mL, range 0.57–2.44, IQR 0.71–1.21). After exclusion of values obtained from four patients with ECMO or Cytosorb(®) adsorber the median concentration was 0.91 µg/mL (range 0.75–2.44, IQR 0.90–1.36) in the RRT group. In addition to previous recommendations we propose to monitor ISA trough plasma concentrations in certain circumstances including RRT, other extracorporeal treatments and obesity.